Aesthetic Evaluation of Restaurants Facade Through Public Preferences and Computational Aesthetic Approach - Herry Santosa; Nur Fauziah (Institut Teknologi Sepuluh Nopember, 2017)
The visual quality of urban space represents the character of the city. Urban space should be able to deliver satisfying aesthetic and sensory experience. The visual quality of urban space formed by the visual signs representing an urban image and influencing the spatial behavior of every individual. A good urban space will encourage the emergence of good perception and meaning, prompting the community to produce a good reaction on its urban spaces. The involvement of public participation in the evaluation and assessment of the visual aesthetics of the urban image is needed to establish a good urban space. This paper investigates the rapid growth of restaurant in the commercial area corridor adjacent to the education campus area in Malang City. Both the location factor and consumers of college students has stimulated the growth of the variety building facade appearances and led to the dominance of contemporary architectural styles. In furtherance of bringing the visual quality of a good urban image, the study on aesthetic aspects is conducted to control the quality visual appearance of the building facade. This study combines the method of public preferences through the Semantic Differential Scales with the computational aesthetic methods through the applications of Interfaces Aesthetic Measurement (IAM) with 13 variables of aesthetic. The results of this study stated that the aesthetic value assessment of building facade restaurants in study area showed a positive value. Furthermore, the comparison of assessment values between the methods of public preferences with the computational aesthetics indicates similarities.